Oxford Energy Forum, Issue 98 - Bassam Fattouh; Ivan Sandrea; Armando Zamora; Thomas Conway (Oxford Energy Forum: A Quarterly Journal for Debating Energy Issues and Policies, 2015)
Latin America is once again on the radar of the international and regional oil and gas industry, service companies, and policy makers. Secular changes in the petroleum investment risk profile of major oil and gas hubs such as Russia, North Africa, West Africa, and the Middle East, limited access to acreage in the traditional producing areas, as well as the lack of new exploration successes outside the emerging provinces such as East Africa and the Eastern Mediterranean, among others, have made Latin America an interesting place to re-visit. These circumstances have coincided with the North American unconventional boom and Mexico's landmark reform that brought the Americas back onto the industry map again. This issue of the Forum covers several regional themes that will shed some light on the challenges and opportunities for the region, as well as some specific country themes.
Keywords: 330